Ensemble fluctuations of the cosmic ray energy spectrum and the intergalactic magnetic field - Supanitsky, Alberto Daniel (2015)
The origin of the most energetic cosmic ray particles is one of the most important open problems in astrophysics. Despite a big experimental effort done in the past years, the sources of these very energeticparticles remain unidentified. Therefore, their distribution on the Universe and even their space density are still unknown. It has been shown that different spatial configurations of the sources lead to different energy spectra and composition profiles (in the case of sources injecting heavy nuclei) at Earth. These ensemble fluctuations are more important at the highest energies, because only nearby sources, which are necessarily few, can contribute to the flux observed at Earth. This is due to the interaction of the cosmic rays with the low energy photons of the radiation field, present in the intergalactic medium, during propagation. It is believed that the intergalactic medium is permeated by a turbulent magnetic field. Although at present it is still unknown, there are several constraints for its intensity and coherence length obtained from different observational techniques. Charged cosmic rays are affected by the intergalactic magnetic field because of the bending of their trajectories during propagation through the intergalactic medium. In this work, the influence of the intergalactic magnetic field on the ensemble fluctuations is studied. Sources injecting only protons and only iron nuclei are considered. The ensemble fluctuations are studied for different values of the density of sources compatible with the constraints recently obtained from cosmic ray data. Also, the possible detection of the ensemble fluctuations in the context of the future JEM-EUSO mission is discussed.